Assessment of Fruit Traits and Antioxidant Capacity in Wild and Cultivated Genotypes of Ziziphus sp. - Radu Liviu Șumălan; Dana Maria Copolovici; Manuela Crișan; Florin Stănică; Renata Maria Șumălan; Andreea Lupitu; Simona Ioana Vicas; Silvia Mot; Lucian Copolovici; Sorin Ciulca (Plants)
The genus Ziziphus includes numerous species, both cultivated and wild, offering significant genetic variability and economic potential that are often overlooked. Due to their high variability and ecological plasticity, jujube species and genotypes can be utilized in marginal areas and on land where few plants could be efficiently exploited. This study investigated variations in morphological characteristics (qualitative and quantitative), bioactive content (e.g., DPPH radicals), and antioxidant capacity in fruits, leaves, and stones of cultivated Z. jujuba genotypes (‘Hu Ping Zao’ and ‘Jun Zao’) and wild genotypes (Z. acido-jujuba and ‘Jurilovca’), using different solvents (water, ethanol, and methanol). The mass and dimensions of the fruits as well as their parameters (fresh and dry weight, length, width, and pulp-to-stone ratio) and the antioxidant potential of different plant organ types (leaves, fruit pulps, and stones) were determined. The results showed that the cultivated genotypes produced larger and heavier fruits with a higher pulp percentage than the wild forms of the same species. However, the wild forms exhibited higher antioxidant capacities than the cultivated genotypes, depending on the type of plant organ analyzed and the solvent used for extraction.